Defining Adult Experiences: Perspectives of a Diverse Sample of Young Adults. (January 2013) - Lowe, Sarah R.; Dillon, Colleen O.; Rhodes, Jean E.; Zwiebach, Liza
This study explored the roles and psychological experiences identified as defining adult moments using mixed methods with a racially, ethnically, and socioeconomically diverse sample of young adults both enrolled and not enrolled in college ( N = 726; ages 18-35). First, we evaluated results from a single survey item that asked participants to rate how adult they feel. Consistent with previous research, the majority of participants (56.9%) reported feeling "somewhat like an adult, " and older participants had significantly higher subjective adulthood, controlling for other demographic variables. Next, we analyzed responses from an open-ended question asking participants to describe instances in which they felt like an adult. Responses covered both traditional roles (e.g., marriage, childbearing; 36.1%) and nontraditional social roles and experiences (e.g., moving out of parent's home, cohabitation; 55.6%). Although we found no differences by age and college status in the likelihood of citing a traditional or nontraditional role, participants who had achieved more traditional roles were more likely to cite them in their responses. In addition, responses were coded for psychological experiences, including responsibility for self (19.0%), responsibility for others (15.3%), self-regulation (31.1%), and reflected appraisals (5.1%). Older participants were significantly more likely to include self-regulation and reflected appraisals, whereas younger participants were more likely to include responsibility for self. College students were more likely than noncollege students to include self-regulation and reflected appraisals. Implications for research and practice are discussed.